Growth Performance and Some Blood Variables of Broiler Chickens Fed Raw or Boiled Mango Kennel Meal - Diarra, S.S.; Usman, B.A. (International Journal of Poultry Science, 2008)
In a 63-day experiment the effect of replacing maize with raw or cooked mango kennel meal on the growth and blood parameters of broiler chickens was investigated. One hundred and eighty (180) day-old Anak, 2000 broiler chicks (mixed sex) were randomly allotted to 3 dietary treatments containing 4 replicates of 15 chicks each. The diets consisted of a maize - based (control) diet and 2 other diets containing 20% of either raw (RMK) or boiled mango kernel (BMK) meal as a replacement for maize. Boiling reduced the toxic factor (tannin) content of mango kernel by up to 75.00%. During the starter phase (0-28 days) birds fed the RMK- based diet ate significantly less feed, gained less weight and recorded a poorer feed conversion ratio (FCR) than the control and the BMK - based diets, but there were no significant dietary effects on these parameters during the finisher period (28-63 days). There were no significant dietary effects on the haematological values but serum total protein and globin were markedly reduced on the RMK fed group. From these results it is concluded that 20% of the maize can be replaced with boiled mango kernel meal in the diet of broilers without adverse effects on growth and blood parameters.